2008
DOI: 10.1051/parasite/2008151093
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of a pyriprole (125 mg/ml) and a metaflumizone (150 mg/ml) combined with amitraz (150 mg/ml) spot-on treatment in preventingPhlebotomus perniciosusfrom feeding on dogs

Abstract: Summary :A controlled clinical trial was performed to assess the effectiveness of a pyriprole (125 mg/ml) and a metaflumizone (150 mg/ml) combined with amitraz (150 mg/ml) spot-on treatment (recommended dosage) in preventing adult female sandflies (Phlebotomus perniciosus) from feeding on dogs. Sandfly mortality was also assessed. Twelve beagle dogs were used in the study. Prior to treatment they were checked for their attractiveness to sandflies, ranked accordingly to generate partner triplets of equivalent s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The three formulations tested, fipronil‐(S)‐methoprene, metaflumizone plus amitraz, and pyriprole, are currently not licensed for the control of mosquitoes and sandflies in dogs. Thomas and others (2008) showed that pyriprole and metaflumizone plus amitraz did not prevent Phlebotomus perniciosus from feeding on dogs; these products could not be proposed for a programme to prevent leishmaniosis in dogs. Similarly, the results of the present study showed that these products did not kill mosquitoes or reduce their blood feeding efficiently.…”
Section: Discussionmentioning
confidence: 99%
“…The three formulations tested, fipronil‐(S)‐methoprene, metaflumizone plus amitraz, and pyriprole, are currently not licensed for the control of mosquitoes and sandflies in dogs. Thomas and others (2008) showed that pyriprole and metaflumizone plus amitraz did not prevent Phlebotomus perniciosus from feeding on dogs; these products could not be proposed for a programme to prevent leishmaniosis in dogs. Similarly, the results of the present study showed that these products did not kill mosquitoes or reduce their blood feeding efficiently.…”
Section: Discussionmentioning
confidence: 99%
“…The use of deltamethrin-impregnated collars in dogs and of nets (with or without insecticides) in human homes and dog kennels is also recommended. A decrease in the prevalence of canine ZVL was observed after 65% permethrin spot-on treatment of dogs (Giffoni et al, 2002) and a significant reduction of anti- Leishmania antibody titers in dogs was observed in dogs using insecticide-impregnated collars (Killick-Kendrick et al, 1997; Maroli et al, 2001; Reithinger et al, 2004) and spot-on repellents (Miró et al, 2007; Ferroglio et al, 2008; Thomas et al, 2008). In southern Europe the use of deltamethrin-impregnated dog collars (Killick-Kendrick et al, 1997; Maroli et al, 2001) is preferred by many dog owners.…”
Section: What Are the Suitable Actions For The Control Of Canine Zvlmentioning
confidence: 99%
“…In southern Europe the use of deltamethrin-impregnated dog collars (Killick-Kendrick et al, 1997; Maroli et al, 2001) is preferred by many dog owners. Alternatively, there is substantial evidence for the efficacy of spot-on repellents containing imidacloprid, permethrin, pyriprole, metaflumizone, or amitraz (Miró et al, 2007; Ferroglio et al, 2008; Thomas et al, 2008). In the Mediterranean region, human and canine cases of ZVL are treated with antiparasitic drugs.…”
Section: What Are the Suitable Actions For The Control Of Canine Zvlmentioning
confidence: 99%
“…44,49 Other chemicals, such as the pyrazole insecticide pyriprole (125 mg/mL) and metaflumizone (an unclassified insecticide; 150 mg/mL) combined with the formamidine amitraz (150 mg/mL) in spot-on formulations, have no or limited efficacy in prevention of P perniciosus from feeding on dogs. 50 Spray formulation-Insecticide activity in spray formulations is immediate after application. In the laboratory setting, spray application of permethrin combined with the insect growth regulator pyriproxyfen yields 87% to 94% protection of dogs from sand fly bites for a 3-to 4-week period (Table 1) 30,33,35 ; however, field studies involving this product have not been reported.…”
Section: Pharmacological Aspects Of Insecticides For Dermal Applicati...mentioning
confidence: 99%